The Study of Tirta Lematang Water Supply Company Services Quality in Lahat Regency: Kualitas Layanan Perusahaan Daerah Air Minum Tirta Lematang di Kabupaten Lahat - Seftiany, Resty; Austin, Trecy (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This research was conducted at the Tirta Lematang Regional Drinking Water Company Lahat. The aim of this research is to measure the quality of service at the Tirta Lematang Regional Drinking Water Company Lahat. In five dimensions of service quality (servqual), namely physical dimensions, reliability, responsiveness, guarantee and empathy, apart from that, it also identifies factors that influence the quality of service for the Tirta Lematang Regional rinking Water Change Lahat. This research is quantitative descriptive with the population being customers and employees of the Tirta Lematang Regional Drinking Water Company with a sample of 100 customers and 67 samples of employees. This research instrument uses a questionnaire. The results using gap analysis show that the gap value of the servqual dimension is negative (<0), so that the service quality of Tirta Lematang is not good. Furthermore, the factors that influence service quality are the availability of service infrastructure/facilities at Tirta Lematang. including using computerization, providing an overview of service flow, human resources related to the presence, commitment and responsiveness of Tirta Lematang officers to provide services. The results of research using SPSS Customer Perceptions and employee perceptions which show differences in results on the assurance dimension on customer perceptions are still considered very low. This has not yet achieved the customer's desire to get service from the Tirta Lematang Regional Drinking Water Company Lahat.